HEAVY METAL BIOSORPTION BY POLYPHENOL-FREE BANANA PEEL POWDER - T. Hussain; M. Imran; Z. Mushtaq; M. I. Khan; M. H. Ahmad; Mahr-Un-Nisa; M. K. Khan (Journal of Animal and Plant Sciences, 2022)
Approach to efficiently manage banana processing waste was proposed by extracting phenolic compound from preserved banana peel powder (PBPP) and then utilizing retentate of this extraction to remove lead and copper from water. The parameters for maximum removal of lead and copper using banana peel retentate (BPR) were optimized in batch biosorption system via response surface methodology (Box-Wilson Design). The optimum values found include: pH, contact time, metal ion concentration and temperature which were 6, 20 min, 20 ppm and 20 ºC for both metals, and bio-sorbent dose of 3 and 1 g/L for lead and copper, respectively. At optimized conditions, reduction of lead and copper (87.30% and 67.50%, respectively) by BPR was lower than by PBPP without phenolic extraction (94.20% and 73.00%). Furthermore, one month storage of vacuum-oven dried banana peel at room temperature showed no significant effect on the yield of polyphenols as well as on the biosorption capacity of banana peel.
Keywords: Banana peel; drying; polyphenols; bio-sorbent; heavy metals